2010
DOI: 10.7205/milmed-d-d0-900145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anterior Knee Pain and Pes Planus in Israel Defense Force Recruits

Abstract: This study examined the prevalence of anterior knee pain (AKP) and pes planus (PP) in Israeli defense force recruits and assessed the relationship between these conditions. We examined the medical records of 97,279 recruits--18,338 females and 78,941 males. The prevalence of AKP was 4.15%. It was lower in females (2.39%) than in males (4.56%). The prevalence of flexible and rigid PP were 15.30% and 0.83%, respectively. The prevalence of both conditions was lower in females (11.31% and 0.34%) than in males (16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, individuals judged as having severe flatfoot (talo-first metatarsal angle greater than 15 degrees on a standing lateral radiograph) serve in the supplementary services. A previous study showed that anterior knee pain was more prevalent in individuals in the armed forces with flexible flat feet than in those with normal feet [ 15 ]. Kaufman et al reported that flat feet are a risk factor for musculoskeletal overuse injury in military trainees [ 16 ], whereas Esterman and Pilotto demonstrated that individuals with flat feet had significantly poorer subjective physical health than those with normal feet [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals judged as having severe flatfoot (talo-first metatarsal angle greater than 15 degrees on a standing lateral radiograph) serve in the supplementary services. A previous study showed that anterior knee pain was more prevalent in individuals in the armed forces with flexible flat feet than in those with normal feet [ 15 ]. Kaufman et al reported that flat feet are a risk factor for musculoskeletal overuse injury in military trainees [ 16 ], whereas Esterman and Pilotto demonstrated that individuals with flat feet had significantly poorer subjective physical health than those with normal feet [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While complaints of ankle pain, knee pain, and back pain are quite common in the pediatric population, these symptoms may be part of a predictable constellation of findings that include low back pain, flexible flat feet, Achilles contracture, and altered gait due to increased lateral subluxation of the patella and hip flexion. While selected reports do exist about a correlation between pes planus, knee pain, and back pain, there is still no data published on the entire above constellation of symptoms [1][2][3]10]. This report details our cohort of patients who presented with back, hip, knee, ankle, or foot pain and their clinical course.…”
Section: Discussionmentioning
confidence: 95%
“…Kosashvili et al studied 92,000 Israeli adolescent military recruits and discovered a link between flat foot severity and the prevalence of anterior knee pain and intermittent low back pain, with moderate and severe flat foot being associated with nearly double the rate of knee and low back pain [1]. In 2010, a follow-up study found a 15.3% incidence of flexible flatfoot among 97,000 Israeli military recruits, with these patients also having a higher rate of anterior knee pain compared to those with flexible pes planus [2]. A third study found that patients with flat feet had 1.3 times the odds of knee pain and 1.4 times the odds of cartilage damage in adults [3].…”
Section: Introductionmentioning
confidence: 99%
“…A population of female homemakers were chosen because as in the earlier studies, Anterior Knee pain is originally a female dominant condition (mainly in adolescent females). Previous studies found out the probable causes for increased incidences of Anterior Knee pain in women may be due to anatomic factors, namely increased Q angle , increased lateral thrust on the patella and decreased muscular strength, hormonal factors like the effects of oestrogen on connective tissue synthesis and postural factors like wearing high heels and sitting with adducted legs, may explain this propensity [1] . However, there were no enough evidences that explained the relationship between lower extremity alignment alteration and Anterior Knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…There were some studies conducted on Military recruits in Israel and one on the Canadian population. [1,5] But there was no study that explained the relationship between Lower extremity alignment alteration (Pes planus) and Anterior knee pain among Obese housewives especially in the Indian population. The main objective of the study was to find whether there is a correlation between Anterior Knee pain and Pes Planus among Obese Homemakers.…”
Section: Discussionmentioning
confidence: 99%